Degradation of endothelial glycocalyx in Tanzanian children with falciparum malaria. Issue 9 (17th August 2021) - Bush, Margaret A.; Florence, Salvatore M.; Yeo, Tsin W.; Kalingonji, Ayam R.; Chen, Youwei; Granger, Donald L.; Rubach, Matthew P.; Anstey, Nicholas M.; Mwaikambo, Esther D.; Weinberg, Joe Brice
Abstract: A layer of glycocalyx covers the vascular endothelium serving important protective and homeostatic functions. The objective of this study was to determine if breakdown of the endothelial glycocalyx (eGC) occurs during malaria infection in children. Measures of eGC integrity, endothelial activation, and microvascular reactivity were prospectively evaluated in 146 children: 44 with moderately severe malaria (MSM), 42 with severe malaria (SM), and 60 healthy controls (HC). Biochemical measures of eGC integrity included plasma syndecan‐1 and total urinary glycosaminoglycans (GAG). Side‐stream dark field imaging was used to quantitatively assess integrity of eGC. Plasma angiopoietin‐2 (Ang‐2) was measured as a marker of endothelial activation and also as a possible mediator of eGC breakdown. Our results show that urinary GAG, syndecan‐1, and Ang‐2 were elevated in patients with MSM and SM compared with HC. Syndecan‐1 and GAG levels correlated significantly with each other and with plasma Ang‐2. The eGC breakdown products also inversely correlated significantly with hemoglobin and platelet count. In the MSM group, imaging results provided further evidence for eGC degradation. Although not correlated with markers of eGC degradation, vascular function (assessed by non‐invasive near infrared spectroscopy [NIRS]) demonstrated reduced microvascular reactivity, particularly affecting the SM group. Our findings provide further evidence for breakdown of eGC in falciparum malaria that may contribute to endothelial activation and adhesion of parasitized red blood cells, with reduced nitric oxide formation, and vascular dysfunction.